Folic acid conjugates with photosensitizers for cancer targeting in photodynamic therapy: Synthesis and photophysical properties. Issue 1 (1st January 2017) - Stallivieri, Aurélie; Colombeau, Ludovic; Jetpisbayeva, Gulim; Moussaron, Albert; Myrzakhmetov, Bauyrzhan; Arnoux, Philippe; Acherar, Samir; Vanderesse, Régis; Frochot, Céline
Graphical abstract: Abstract: Recent researches in photodynamic therapy have focused on novel techniques to enhance tumour targeting of anticancer drugs and photosensitizers. Coupling a photosensitizer with folic acid could allow more effective targeting of folate receptors which are over-expressed on the surface of many tumour cells. In this study, different folic acid–OEG-conjugated photosensitizers were synthesized, characterized and their photophysical properties were evaluated. The introduction of an OEG does not significantly improve the hydrophilicity of the FA–porphyrin. All the FA-targeted photosensitizers present good to very good photophysical properties. The best one appears to be Ce6. Molar extinction coefficient, fluorescence and singlet oxygen quantum yields were determined and were compared to the corresponding photosensitizer alone.